Meldonium Ameliorates Hypoxia-Induced Lung Injury and Oxidative Stress by Regulating Platelet-Type Phosphofructokinase-Mediated Glycolysis - Wang, Daohui; Liu, Fengying; Yang, Weijie; Sun, Yangyang; Wang, Xiaoning; Sui, Xin; Yang, Jun; Wang, Qian; Song, Wenhao; Zhang, Minmin; Xiao, Zhenyu; Wang, Tian; et al. (Frontiers in Pharmacology, 2022)
Hypoxic environments at high altitudes influence the long-term non-altitude health of residents, by inducing changes in metabolism and the mitochondria, severe lung injury, and endangering life. This study was aimed to determine whether meldonium can ameliorate hypoxia-induced lung injury and investigate its possible molecular mechanisms. We used Swiss mice and exposed type Ⅱ alveolar epithelial cell to hypobaric hypoxic conditions to induce lung injury and found that meldonium has significant preventive effect, which was associated with the regulation of glycolysis. We found using human proteome microarrays assay, molecular docking, immunofluorescence and pull-down assay that the target protein of meldonium is a platelet-type phosphofructokinase (PFKP), which is a rate-limiting enzyme of glycolysis. Also, meldonium promotes the transfer of nuclear factor erythroid 2-related factor 2 (Nrf2) from the cytoplasm to the nucleus, which mitigates oxidative stress and mitochondrial damage under hypoxic condition. Mechanistically, meldonium ameliorates lung injury by targeting PFKP to regulate glycolysis, which promotes Nrf2 translocation from the cytoplasm to the nucleus to alleviate oxidative stress and mitochondrial damage under hypoxic condition. Our study provides a novel potential prevention and treatment strategy against hypoxia-induced lung injury.